An early measuring of the Holy City, forgotten for over a century: Westphal’s Jerusalem map of 1825 - Goren, Haim; Schelhaas, Bruno (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
In 1822 and 1823 three young German scholars, Peter von Medem, Gustav Parthey and Johann Heinrich Westphal, undertook a research expedition to Egypt and Palestine. One major result of this journey was a very accurate map of Jerusalem: “Jerusalem und seine nächsten Umgebungen” (“Jerusalem and its environs”), published in 1825 by Heinrich Berghaus in his journal Hertha. Together with Franz Wilhelm Sieber’s plan of 1818 this map belongs to the very first “modern” maps of Jerusalem, based on measurements and new scientific research results. In addition, the sketches, as well as extracts from Parthey’s and von Medem’s diaries, formed the material for Berghaus’ memoir to his Map of Syria in 1835. This article deals with the background of the voyage, the production, publication and reception of the map, and the complex network of actors involved, based on recently discovered archival sources. Moreover, the map became forgotten in the 19th and 20th centuries. Apart from Berghaus, the map was actually never used by later cartographers of Jerusalem and no longer mentioned in studies concerning the history of the city’s modern cartography.